SIMULASI POLA OPERASI TANDON AIR UNTUK PENYEDIAAN AIR BERSIH PADA KECAMATAN LAPE KABUPATEN SUMBAWA BESAR - Taufiq, Mohammad; WS, Anggara W.; Siswoyo, Hari (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2012)
In effort to fulfill water needs in the Subdoistrict of Lape District of Sumbawa Besar harnesseda source of water wellsdug with the discharge capacity of 1.5 liters/sec. Services of water using a pump sistem with the storage water tower. Due to the small discharge capacity, then simulation of water conditions instorage water toweris used to determine the pattern to be used in the operation of water services.Keywords: Water, well dug, pump, reservoir, simulation